2008
DOI: 10.2340/00015555-0323
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Onychomycosis among Psoriatic Patients in Israel

Abstract: Published data on the prevalence of onychomycosis in psoriasis patients compared with healthy controls are controversial, We therefore conducted a prospective study of toenail onychomycosis, among 113 psoriatic and 106 healthy non-psoriatic subjects, selected from the normal population in the Jerusalem area in the period 2003-05. The results revealed a prevalence of 47.6% toenail onychomycosis among psoriatic patients, compared with 28.4% in normal controls (p=0.0054). Both gender and age affected the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 13 publications
(13 reference statements)
5
42
0
6
Order By: Relevance
“…[2] found toenail onychomycosis in 13% of psoriatic individuals without nail involvement; the frequency of fungal nail infection in patients suffering from psoriasis with the presence of nail abnormalities was higher and reached 27%. Other studies have shown an even higher prevalence of up to 47% toenail onychomycosis among psoriatic patients, compared with 28.4% in normal controls 3–7 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[2] found toenail onychomycosis in 13% of psoriatic individuals without nail involvement; the frequency of fungal nail infection in patients suffering from psoriasis with the presence of nail abnormalities was higher and reached 27%. Other studies have shown an even higher prevalence of up to 47% toenail onychomycosis among psoriatic patients, compared with 28.4% in normal controls 3–7 …”
Section: Discussionmentioning
confidence: 93%
“…The frequency of onychomycosis in psoriatic patients with nail involvement ranges from 13% to 47% 2–7 . Nail abnormalities, especially in psoriatic patients, may cause cosmetic problems with psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies examined risk factors associated with onychomycosis in children and these included being male, being over age 10 years and some characteristics associated with socioeconomic conditions (living in a rural area, having a father who is unemployed, living in a house with less than three rooms and having greater than three siblings) . For psoriasis patients, the type and duration of psoriasis was significantly associated with onychomycosis . Specifically, the prevalence of onychomycosis was higher in patients with plaque‐type psoriasis compared with palmo‐plantar psoriasis and the longer the psoriasis was present, the greater the risk of onychomycosis .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of onychomycosis in psoriatic patients was ascertained from patients with and without confirmed psoriatic nail involvement and this prevalence estimate increased when only those patients with nail psoriasis are included . Studies reported mixed findings regarding the prevalence of onychomycosis in psoriatic patients, with both higher and lower estimates reported relative to the general population …”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have aimed to investigate the prevalence of Candida colonization in different body sites of patients with psoriasis but have varied in their results . Recent studies have considered psoriasis as an immunological skin disease that involves substantial changes in humoral immune response .…”
Section: Introductionmentioning
confidence: 99%